(*)Biomimetic Mineralization of Biomaterials Using Simulated Body Fluids for Bone Tissue Engineering and Regenerative Medicine - Shin, Kyungsup (Tissue Eng Part A, 2017)
Development of synthetic biomaterials imbued with inorganic and organic characteristics of natural bone that are capable of promoting effective bone tissue regeneration is an ongoing goal of regenerative medicine. Calcium phosphate (CaP) has been predominantly utilized to mimic the inorganic components of bone, such as calcium hydroxyapatite, due to its intrinsic bioactivity and osteoconductivity. CaP-based materials can be further engineered to promote osteoinductivity through the incorporation of osteogenic biomolecules. In this study, we briefly describe the microstructure and the process of natural bone mineralization and introduce various methods for coating CaP onto biomaterial surfaces. In particular, we summarize the advantages and current progress of biomimetic surface-mineralizing processes using simulated body fluids for coating bone-like carbonated apatite onto various material surfaces such as metals, ceramics, and polymers. The osteoinductive effects of integrating biomolecules such as proteins, growth factors, and genes into the mineral coatings are also discussed.